Efektivitas Youtube Dalam Meningkatkan Komunikasi Interpersonal Siswa SDN Karagdinoyo 2 Kecamatan Sumberrejo Kabupaten Bojonegoro - sumunik*, sumunik; Widyastono, Herry; Santosa, Eka Budhi (Universitas Syiah Kuala, 2023)
In current learning, the use of information technology is a major need, one of which is the use of YouTube media. The use of information technology in the form of learning videos from YouTube can have an impact on interaction abilities and communication patterns during the learning process. This research aims to determine the effectiveness of using YouTube media in improving interpersonal communication for elementary school age children at Publict Elementaru School Karangdinoyo 2 Sumberrejo Bojonegoro. This research uses a quantitative approach and the research method used is quasi-experimental with a One Group Pretest-Posttest Only Design research design, namely that the experimental group and control group were not chosen randomly and only the experimental class received treatment while the control class received no treatment. The sample in the experimental class was 25 people and the control class was 25 people. Data collection techniques use questionnaires Likert scale model. The data analysis technique uses the t test. The results of the t test calculations found t count t table, (3.16 2.01) so it can be concluded that YouTube media is effective (influential) in improving interpersonal communication for students at Publict Elementaru School Karangdinoyo 2.